What drives non-linguists' hands (or mouse) when drawing mental dialect maps? - Jeszenszky, Péter; Steiner, Carina; Allmen, Nina von; Leemann, Adrian (Digital Scholarship in the Humanities, 2024)
In perceptual dialectology, mental mapping is a popular tool used for eliciting attitudes and the spatial imprint of linguistic cognition from non-linguists, through tasking them with drawing about linguistic variations on maps. Despite the popularity of this method, research on the geometrical parameters of the shapes drawn on these maps has been limited. In our study, we utilized 500 mental maps, both digital and hand-drawn, introducing a new digital implementation for mental mapping (source code available). Our contribution presents the first perceptual dialectological outcomes of the 'Swiss German Dialects in Time and Space' project, which recorded a socio-demographically balanced corpus containing a large amount of quantitative personal data about participants that represent the entire Swiss German dialect continuum. Our first research question explores how various sociolinguistic variables and other variables related to personal background influence the geometrical parameters of shapes drawn, such as the number of shapes, their coverage of the language area, and their compactness. Statistical modelling reveals that dialect identity plays the most important role, while educational background, urbanity, and regional differences also affect more parameters. The second research question investigates the comparability between hand-drawn and digital mental maps, showing that they are generally comparable in terms of geometrical aspects, with minor limitations due to specific technical considerations in our digital method.